EVALUASI KESUBURAN TANAH SAWAH DI DESA RANOKOLO KECAMATAN MAUROLE KABUPATEN ENDE - Yeremias Dala; Charly Mutiara (AGRICA, 2019)
Land that was managed by intensively will effect decreasing soil fertility. This condition happened in the rice fields in Ranokolo Village, Maurole District, Ende Regency. This study aims to determine the fertile of paddy soil, and the soil chemical criteria in the village have been carried out. This study uses a survey method, which is to determine the soil sample taken using the purposive sampling method. With this method obtained 13 research sites. Soil sampling in this study using soil samples that operated. And the replaced variables are C-Organic, available K, total P, cation exchange capacity (CEC), and Base Saturation (BS). The results showed, the C-Organic variable in Ranokolo Village, Maurole District, is classified as low, K as moderate, P-total as high, CEC is moderate, and Saturation of Bases as moderate. From the results of soil fertility analysis, the criteria for soil fertility in Ranokolo Village, Maurole District, Ende Regency is low with a C-Organic limiting factor.